Lack of Association of a Functional Polymorphism in the Serotonin Receptor Gene With Body Mass Index and Depressive Symptoms in a Large Meta-Analysis of Population Based Studies - Brummett, Beverly H.; Babyak, Michael A.; Singh, Abanish; Hauser, Elizabeth R.; Jiang, Rong; Huffman, Kim M.; Kraus, William E.; Shah, Svati H.; Siegler, Ilene C.; Williams, Redford B. (Frontiers in Genetics, 2018)
The serotonin receptor 5-HTR2C is thought to be involved in the function of multiple brain structures. Consequently, the HTR2C gene has been studied extensively with respect to its association with a variety of phenotypes. One coding variant in the HTR2C gene, Cys23Ser (rs6318), has been associated with depressive symptoms and adiposity; however, these findings have been inconsistent. The reasons for this mixed picture may be due to low statistical power or due to other factors such as failure to account for possible interacting environmental factors, such as psychosocial stress. Further, the literature around this polymorphism is marked by limited inclusion of persons of African ancestry. The present study sought to overcome these limitations and definitively determine the relationship of this polymorphism with depressive and obesity phenotypes in a large sample meta-analysis. Thus, we harmonized individual level data from 10 studies including the Women’s Health Initiative, CARDIA, ARIC, Framingham Offspring, and the Jackson Heart Study, resulting in a sample of 27,161 individuals (10,457 Black women, 2,819 Black men, 7,419 White women, and 6,466 White men). We conducted a random effects meta-analysis using individual level data to examine whether the Cys23Ser variant—either directly, or conditionally depending on the level of psychosocial stress—was associated with depressive symptoms and body mass index (BMI). We found that psychosocial stress was associated with both depression and BMI, but that Cys23Ser was not directly associated with, nor did it modify the associations of psychosocial stress with depression or BMI. Thus, in the largest study of this polymorphism, we have determined that rs6318 is not associated with depression or BMI.